Epigenetic Methylation of Parathyroid CaR and VDR Promoters in Experimental Secondary Hyperparathyroidism - Jacob Hofman-Bang; Eva Gravesen; Klaus Olgaard; Ewa Lewin (International Journal of Nephrology)
Secondary hyperparathyroidism (s-HPT) in uremia is characterized by decreased expression in the parathyroids of calcium sensing (CaR) and vitamin D receptors (VDR). Parathyroid hormone (PTH) is normalized despite low levels of CaR and VDR after experimental reversal of uremia. The expression of CaR in parathyroid cultures decreases rapidly. Methylation of promoter regions is often detected during epigenetic downregulation of gene expression. Therefore, using an experimental rat model, we examined changes in methylation levels of parathyroid CaR and VDR promoters in vivo and in vitro. Methods. Uremia was induced by 5/6 nephrectomy. Melting temperature profiling of CaR and VDR PCR products after bisulfite treatment of genomic DNA from rat parathyroids was performed. Real-time PCR measured expression of PTH, CaR, VDR, and klotho genes in vitro. Results. Parathyroids from uremic rats had similar low levels of methylation in vivo and in vitro. In culture, a significant downregulation of CaR, VDR, and klotho within two hours of incubation was observed, while housekeeping genes remained stable for 24 hours. Conclusion. In uremic s-HPT and in vitro, no overall changes in methylation levels in the promoter regions of parathyroid CaR and VDR genes were found. Thus, epigenetic methylation of these promoters does not explain decreased parathyroid expression of CaR and VDR genes in uremic s-HPT.